ENTANGLED INVASIVE LIVES: INDIGENOUS INVASIVE PLANT MANAGEMENT IN NORTHERN AUSTRALIA. Issue 2 (June 2015) - Head, Lesley; Atchison, Jennifer
ABSTRACT This article explores the entanglement of two kinds of invasive lives in northern Australia: invasive plants, and the enduring life of the unfinished colonial project, which continues to have implications for indigenous peoples. In the extensive indigenous lands of Australia's tropical north, communities have increasing responsibility for invasive plant management among other pressing land management tasks. In a context of climate change and novel ecosystems, these entanglements exacerbate environmental management challenges in the tropical savanna and affect indigenous livelihoods. Drawing on arguments that it is necessary to literally speak novel ecologies, we here enunciate and describe a novel ecological assemblage we call Indigenous Invasive Plant Management (IIPM). Historical accounts and contemporary ethnography (semi‐structured interviews and participant observation undertaken in 2010–2013) show a lingering colonial heritage in the ways that IIPM is entwined with tenure and governance issues, and in its everyday practice. These findings illustrate how IIPM can risk being a form of continuing dispossession as well as having good potential outcomes.